Isolation, Screening, Characterization and Antagonism Assay of PGPR Isolates from Rhizosphere of Rice Plants in Cuddalore District - M, Manivannan (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Plant growth-promoting rhizobacteria (PGPR) are beneficial bacteria that colonize plant roots and enhance plant growth by a wide variety of mechanisms. The use of PGPR is steadily increasing in agriculture and offers an attractive way to replace chemical fertilizers, pesticides, and supplements. Here, we have isolated, screened and characterized the PGPR from the rhizosphere soil of rice field. Rhizosphere soils were collected from different areas of Cuddalore district in Tamil Nadu, India. Ten isolates of bacteria, designated as PGB1, PGB2, PGB3, PGB4, PGB5, PGT1, PGT2, PGT3, PGG1 and PGG2, were successfully isolated and characterized. Subsequently, to investigate the PGPR isolates for their antagonistic activity against phytopathogenic fungi such as Fusarium oxysporum, Rhizoctonia solani and Sclerotium rolfsii. In extend, the growth of PGPR isolates was optimized under different temperature conditions such as 10°C, 20°C, 28°C, 37°C and 45°C. Isolates PGB4, PGT1, PGT2, PGT3, PGG1 and PGG2 induced the production of indole acetic acid (IAA), whereas only PGT3 isolate was able to solubilize phosphorus. In case of Siderophore production, the isolates PGB4, PGT1, PGT2, PGT3 and PGG2 were found to be positive. Most of the isolates grown best under the temperature of 20°C & 28°C when compared to 10°C & 37°C and very few can grown at 45°C. Furthermore, most of the PGPR isolates shown antifungal activity against Fusarium oxysporum, and Rhizoctonia solani, and only one against Sclerotium rolfsii. The present study, therefore, suggests that the use of PGPR isolates PGB4, PGG2 and PGT3 as inoculants/ biofertilizers might be beneficial for rice cultivation as they enhanced growth of rice due to the production of IAA, Phosphate solubilization, Siderophore production and also having antifungal activity against phytopathogenic fungi.